2021
DOI: 10.1002/aisy.202000240
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Responsive Soft Actuators with Integrated Sensing Function Based on 1T‐MoS2 Composite

Abstract: Soft actuators can respond to electricity, [1][2][3][4] light, [5][6][7][8] heat, [9,10] and humidity [11,12] and produce mechanical deformation output. Owing to a wide range of applications in soft robots, [13] intelligent biomimetic devices, [14,15] biomedical sensing and diagnosis, [16] and wearable devices, [17] they have received more and more research interests recently. According to the external stimuli and actuation mechanism, soft actuators can be divided into many types, such as electrical-induced ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…The actuation magnitude can be modulated by the light intensity (Figure S9C, Supporting Information), and the performance compares favorably with other sensing actuators (see Table 2 ). [ 14,16,18–21,34,37–40 ] In addition to actuation, vis light also induces resistive changes as shown in Figure 2F. Here, upon illumination by vis light of ≈65 mW cm −2 for 5 s, the trilayer film bent by an angle change of ≈360° by the actuating strain of TMO/H layer at ≈−0.32% (see details in the Supporting Information), with a simultaneous Δ R / R of −4.5%.…”
Section: Resultsmentioning
confidence: 94%
“…The actuation magnitude can be modulated by the light intensity (Figure S9C, Supporting Information), and the performance compares favorably with other sensing actuators (see Table 2 ). [ 14,16,18–21,34,37–40 ] In addition to actuation, vis light also induces resistive changes as shown in Figure 2F. Here, upon illumination by vis light of ≈65 mW cm −2 for 5 s, the trilayer film bent by an angle change of ≈360° by the actuating strain of TMO/H layer at ≈−0.32% (see details in the Supporting Information), with a simultaneous Δ R / R of −4.5%.…”
Section: Resultsmentioning
confidence: 94%
“…[114] Alternatively, Yao et al reported a programmable actuator by attaching stiff materials to the high CTE layer, as shown in Figure 5e. [113] In addition, there are many novel methods, such as the use of the anisotropic expansion of actuating materials (Figure 5f) [130] or multiresponse materials [131][132][133][134][135] to control the shape output.…”
Section: Bilayer Etasmentioning
confidence: 99%
“…3) The self-sensing gripper allows sensing without extra external sensors; it can be programmed and miniaturized for specific tasks and applications. Ji et al [8] developed a composite film-based gripper that could bend as well as strain sensing. Bombara et al [9] used a twisted string actuator to achieve position self-sensing of the gripper.…”
Section: Introductionmentioning
confidence: 99%